Oscillations of fatty acid and glycerol release from human subcutaneous adipose tissue in vivo. - Karpe, F; Fielding, B; Coppack, S; Lawrence, V; Macdonald, I; Frayn, K (2005)
We sought evidence for pulsatility of lipolysis in human subcutaneous adipose tissue in vivo. Arterialized and adipose tissue venous blood samples were drawn at 2-min intervals from nine healthy subjects. This procedure was repeated during hyperinsulinemic-euglycemic clamp to remove insulin pulsatility. We found evidence for pulsatile release of both nonesterified fatty acids (NEFAs) (seven of nine subjects) and glycerol (five of six subjects) with a period of approximately 12-14 min. This pulsatility was maintained even during the hyperinsulinemic clamp. Checks were made for spurious pulse detection, including the creation of "mock" venoarterialized differences by subtracting one subject's arterialized concentrations from another's venous; the peaks detected were less consistent in character than with real data (peak width, P = 0.006; peak interval, P < 0.004). Significant cross-correlations between NEFA and glycerol release also provided evidence of a real effect. Arterialized norepinephrine concentrations were also pulsatile, but the period did not match that of NEFA and glycerol release. Insulin concentrations were pulsatile with a typical period of 12 min, but this was not significantly cross-correlated with lipolysis. We conclude that release from adipose tissue of the products of lipolysis is pulsatile in humans.